The effects of perceived organizational support and perceived supervisor support on employee turnover - Maertz Jr, Carl P.; Griffeth, Rodger W.; Campbell, Nathanael S.; Allen, David G. (Journal of organizational behavior, 2007)
This study examines mediated effects of perceived supervisor support (PSS) and perceived organizational support (POS) on turnover cognitions, and their interactive effects on turnover behavior in a sample of 225 social services workers. In this study, we address a seeming contradiction in current findings regarding support and attachments to managers versus attachments to the organization itself. The POS literature suggests fully mediated causal paths to turnover from POS and PSS, through affective commitment. Whereas, the commitment, LMX, and turnover literatures suggest alternative causal paths that imply broader effects for POS and PSS on turnover. Contrary to earlier POS literature, findings showed that PSS had independent effects on turnover cognitions not mediated through POS. Model tests also indicated that POS had significant effects on turnover mediated through normative commitment, as well as affective organizational commitment. Moreover, a new significant interactive relationship was discovered such that low PSS strengthened the negative relationship between POS and turnover, while high PSS weakened it. Implications for research and practice are discussed.